PENGAJUAN DAN PEMBERIAN HAK RESTITUSI BAGI ANAK YANG MENJADI KORBAN KEJAHATAN SEKSUAL - Sapti Prihatmini; Fanny Tanuwijaya; Dina Tsalist Wildana; Misbahul Ilham (RechtIdee, 2019)
This paper aims to analyze the mechanism for submitting and granting restitution as the responsibility of perpetrators of crimes. This is to fulfill the rights of children who are victims of criminal acts. The implemented provisions governing the submission and granting of restitution are regulated in PP No. 44 of 2008 and PP No. 43 of 2017. However, the implementation of the restitution provision,which is the right of the child (victim), has not been fully implemented due to a lack of maximum assistance by the relevant government, such us fulfilling the rights of victims to obtain rehabilitation, compensation and restitution as a form of protection of children after the occurrence of a crime for the loss suffered by the child and / or the family of the victim. This study uses doctrinal research (doctrinal legal research), while the approach used is (socio-legal studies) an effort to explore a problem by not only fulfilling the study of legal norms or doctrines, but also looking comprehensively at the context of norms and enforcement. The results showed that the submission of restitution stipulated in Government Regulation No. 43 of 2017 outlines that restitution is a compensation payment charged to the perpetrator based on a court decision.  It  has permanent legal force for material and immaterial losses suffered by the victim or his family, as in the case of giving restitution for a non specifically regulated the period of payment and a rejection of payments from perpetrators of sexual crimes.